Myocardial ischemia on the background of paroxysmal atrial fibrillation: result of arrhythmia or sign of coronary atherosclerosis? - I. S. Metelev; O. V. Soloviev; E. L. Onuchina; S. K. Kononov (Лечащий Врач, 2021)
Prevalence of coronary atherosclerosis in patients with features of acute myocardial ischemia on the background of paroxysmal atrial fibrillation and suspected non-ST elevation acute coronary syndrome was evaluated. Clinical and laboratory predictors of significant coronary atherosclerosis in patients of this group were suggested. Negative impact of coronary atherosclerosis in patients with paroxysmal atrial fibrillation was shown.